Gall Wasps, Callirhytis quercusclaviger (Ashmead) and Callirhytis cornigera (Osten Sacken) (Insecta: Hymenoptera: Cynipidae) - Wayne N. Dixon (EDIS)
EENY-368, a 5-page illustrated fact sheet by Wayne N. Dixon, describes the distribution, identification, biology, economic importance, symptoms, and management of this family of oak tree pests. Includes bibliographic references. This publication has been published as DPI Entomology Circular 355 (Nov. 1992) and is also available on the Featured Creatures Web site by the UF Department of Entomology and Nematology, May 2006.